Studi Pengelolaan Keuangan pada iGeneration - Nur, Shafina Ayanda; Wulandari, Dewi Ayu (Jurnal Ilmu Manajemen, 2024)
iGeneration or commonly known as Generation Z understands the importance of financial management, but there are still many who can’t do it well. This is because currently there are life trends in Generation Z, namely You Only Live Once (YOLO) and Fear of Missing Out (FOMO) which can effect their financial management. Financial management should be well implemented starting from the younger generation who have entered productive age or Generation Z. Therefore, this study aims to analyze the effect of financial literacy, lifestyle, gender and education on financial management of Generation Z. This study uses quantitative research methods with primary data obtained through distributing questionnaires. The population of this study is Generation Z who already have an income and live on Java Island. This study uses 135 respondents taken using purposive sampling technique. This study uses statistical and descriptive analysis techniques with Partial Least Square (PLS) and Independent Sample t Test. The result of this study shows that financial literacy and education have a significant positive effect on financial management of Generation Z. Lifestyle has a significant negative effect on financial management of Generation Z. There is no difference in financial management between men and women in Generation Z.